2019
DOI: 10.1002/jhbp.688
|View full text |Cite
|
Sign up to set email alerts
|

Single‐session multiple stent deployment using moving cell stent without dilating initial stent mesh to treat malignant hilar biliary obstruction (with videos)

Abstract: Background Malignant hilar biliary obstruction (MHBO) can be treated with bilateral self-expandable metal stents (SEMS) deployed using side-by-side (SBS) or stent-instent (SIS) techniques. Moving cell stents (MCS) are a novel type of SEMS. The present study evaluated the technical feasibility of treating MHBO using bilateral novel uncovered SEMS to insert an SIS technique without dilating the mesh of a first stent within a single session. Method We retrospectively assessed patients who were complicated with ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…Patients with unresectable cholangiocarcinoma always need biliary drainage with endoscopic biliary stenting; however, stent deployment is technically complex when more than one stent is needed. [25][26][27] Furthermore, the recurrent biliary obstruction rate after stent deployment has been reported as 20%-55%, which needs reintervention. 5 In such cases, IRE can be applied with endoscopy as an adjunct treatment before stent deployment and is expected to reduce the difficulty of stent deployment and prolong the stent patency duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with unresectable cholangiocarcinoma always need biliary drainage with endoscopic biliary stenting; however, stent deployment is technically complex when more than one stent is needed. [25][26][27] Furthermore, the recurrent biliary obstruction rate after stent deployment has been reported as 20%-55%, which needs reintervention. 5 In such cases, IRE can be applied with endoscopy as an adjunct treatment before stent deployment and is expected to reduce the difficulty of stent deployment and prolong the stent patency duration.…”
Section: Discussionmentioning
confidence: 99%
“…Although biliary injury has been observed in several studies, the application of IRE ablation for the treatment of biliary malignant tumors has potential advantages. Patients with unresectable cholangiocarcinoma always need biliary drainage with endoscopic biliary stenting; however, stent deployment is technically complex when more than one stent is needed 25‐27 . Furthermore, the recurrent biliary obstruction rate after stent deployment has been reported as 20%–55%, which needs reintervention 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, PTBD or transpapillary approach might be suitable. Especially in transpapillary approach in patients with normal anatomy, there have been multiple reports regarding preoperative drainage, 14 novel concepts or novel SEMS for higher technical success or longer patency 15–20 and factors affecting reintervention success, 21 although surgically altered anatomy surely restrict the validity of those reports even with application of balloon‐assisted endoscopies. Although our study showed similar efficacy and safety between EUS‐ABS and PTBD in the management of unresectable DMBO in patients with surgically altered anatomy, the choice of drainage method can be cautiously made based on the above‐mentioned features of each drainage method, physician expertise, and patient condition, particularly biliary obstruction location.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various biliary cannulation techniques have been described, such use of a double guidewire or physician-controlled guidewire technique, and techniques for metal stent deployment to treat malignant hilar biliary obstruction, such as stent-in-stent, side-by-side, or hybrid stent deployment techniques in endoscopic retrograde cholangiopancreatography (ERCP) procedures [1][2][3][4][5][6]. Recently, interventional endoscopic ultrasound (EUS), such as hepaticogastrostomy, choledochoduodenostomy, or pancreatic transluminal drainage, has also been developed [7,8].…”
Section: Introductionmentioning
confidence: 99%